Urban data and definitions in sub-Saharan Africa: Mismatches between the pace of urbanisation and employment and livelihood change. (April 2018) - Potts, Deborah
Differing definitions of 'urban' settlements can make comparative analysis of trends in urbanisation difficult. Definitions used by many African countries include small settlements which may not exhibit the degree of labour specialisation away from agriculture that economic theories about urbanisation presume. This may mean there is a mismatch if urban data are presumed by decision-makers to be proxies for structural economic transformation. After examining these definitional issues this paper provides five illustrative African case studies based on detailed analysis of census and agricultural employment data. It finds that for Côte d'Ivoire, Ghana and Mali in situ urbanisation of settlements at the bottom of the urban hierarchy has played a significant part in recent urbanisation processes. In Rwanda complex boundary changes have also contributed to a very significant redefinition of previously rural people as 'urban' yet overall the urbanisation level did not increase between 2002 and 2012. Significant employment in agriculture is found within small, and some larger, urban centres in all these countries. It is shown that these issues tend to be disregarded in analyses of urban trends for these countries which often present a more positive narrative of urban economic change than the census data support. These examples are contrasted with Botswana, where in situ urbanisation has also occurred but in this case driven by real occupational change. The paper concludes that the impact of definitions on apparent trends in urbanisation in Africa needs to be understood given the significance attached to these trends by policy makers.